Midget Cities: Utopia, Utopianism and the Vor-schein of the 'Freak' Show. - Howells, Richard; Chemers, Michael (Disability Studies Quarterly, 2005)
In the early half of the 20th century, World's Fairs sprang up periodically across the United States. One corollary to these colossal exhibitions was the emergence of the phenomenon of "Midget Cities," sites connected to the Fairs where professional performers of short stature would gather to work, and live, in communities constructed to be miniature representations of "normal" scale buildings. This article is an historical account of the three largest Midget Cities of the United States of the 20th century. We then proceed with a theoretical analysis of both our specific case-studies and of the freak show in general, guided by the German Utopian thinker Ernst Bloch. Along the way we consider the advantages of Midget Cities to their residents and performers, together with the utility (or lack thereof) of recovering the occult history of the "freak show" to disabled people in general. We conclude by contemplating the usefulness of a Utopian analysis of "freakery" to the community, inclusive of but not limited to, both disability and its study.